Experimental investigation of the angle of attack dependence of the flow past a cactus-shaped cylinder with four ribs. Issue 208 (January 2021) - Zhdanov, Oleksandr; Green, Richard; Busse, Angela
Abstract: The aerodynamic properties of a two-dimensional cactus-shaped cylinder with four ribs are studied experimentally. The cross section of the cylinder corresponds to a modified square cylinder with rounded corners and concave sides inspired by tall succulents with four ribs. The mean aerodynamic coefficients, fluctuating lift coefficient, Strouhal number, and mean surface pressure distribution are measured as a function of the angular orientation for Reynolds numbers ranging from 50, 000 to 150, 000. Hot-wire measurements are conducted at two locations in the wake for several angles of attack to provide insight into the vortex shedding frequencies. The results show that the studied shape exhibits a strong angle of attack dependence while no Reynolds number dependence is found within the tested range. As for the square cylinder, a critical angle of attack of approximately 13° is observed at which drag and fluctuating lift forces are minimised while mean lift and Strouhal number reach their highest values. Reattachment of the shear layer at and above the critical angle of attack is confirmed using PIV. Overall, succulents with four ribs retain some of the aerodynamic benefits that have been observed for cactus-shaped cylinders with many ribs, albeit over a limited range of angles of attack. Graphical abstract: Image 1 Highlights: Experimental investigation of aerodynamics of a cactus-shaped cylinder with 4 ribs No Reynolds number dependence is observed in tested range (50, 000 to 150, 000) Cactus-shaped cylinder exhibits a strong angle of attack dependence Critical angle of attack is close to values reported for the square cylinder Critical angle of attack is associated with reattachment of separated shear layer